2018
DOI: 10.3390/nu10030367
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Dietary Interventions on Calcitriol, Parathyroid Hormone, Calcium, and Phosphorus: Results from the DASH Trial

Abstract: The “Dietary Approaches to Stop Hypertension” (DASH) diet, rich in fiber and low-fat dairy, effectively lowers blood pressure. DASH’s effect on calcitriol and other markers of bone-mineral metabolism is unknown. This secondary analysis of the DASH trial aimed to determine the effect of dietary patterns on blood concentrations of calcitriol, parathyroid hormone (PTH), ionized calcium, and urinary excretion of calcium and phosphorus. Outcomes were available in 334 participants in the trial. After a 3-week run-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
5
1
Order By: Relevance
“…Once increases in PTH activate bone remodeling, increasing blood calcium levels, a decrease in PTH may be beneficial, favoring the aggregation of calcium in the bones, whereas this mineral exerts feedback inhibition on the PTH glands as well [57]. In this study, the DieTBra improved levels of this bone marker, suggesting a better balance of PTH levels after a nutritional intervention with a healthy dietary pattern, different from another study with the Dietary Approaches to Stop Hypertension (DASH), in which there was an increase only in calcitriol levels without a difference for PTH and further bone parameters during three weeks of follow-up [58].…”
Section: Discussioncontrasting
confidence: 62%
“…Once increases in PTH activate bone remodeling, increasing blood calcium levels, a decrease in PTH may be beneficial, favoring the aggregation of calcium in the bones, whereas this mineral exerts feedback inhibition on the PTH glands as well [57]. In this study, the DieTBra improved levels of this bone marker, suggesting a better balance of PTH levels after a nutritional intervention with a healthy dietary pattern, different from another study with the Dietary Approaches to Stop Hypertension (DASH), in which there was an increase only in calcitriol levels without a difference for PTH and further bone parameters during three weeks of follow-up [58].…”
Section: Discussioncontrasting
confidence: 62%
“…Cheung et al (45) suggested that low dietary magnesium intake could alter the vitamin D-PTH relationship in adults who were overweight or obese. In another study assessing the effect of the dietary approaches to stop hypertension (DASH) diet, which is rich in fiber and low-fat dairy and is useful for lowering blood pressure on the PTH level, no significant effect was observed (46). Additionally, the cause-and-effect relationship between PTH and inflammation still remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Study stratification by health outcomes is depicted in Figure 2. 41 , calcitriol (men only) 31 , TC, LDL and HDL 35 , and CHD risk 25 on the DASH diet in Black people compared to Whites. In the DASH-sodium study, the reductions in BP between the lower and higher sodium levels on the control diet were greater in Black people versus Whites 47 .…”
Section: Effects Of Dietary Intervention On Health Outcomes By Race or Ethnicitymentioning
confidence: 99%